English Civil War Politics and the Religious Settlement - Kaplan, Lawrence S. (Church history, 1972)
One of the more active historical controversies centers around the precise relationship of religion to politics during the period of the English Civil War. While all historians recognize the crucial role played by Puritans in the rebellion against Charles I, the extent to which religious considerations influenced political activity within the Long Parliament remains open to question. A major reason for the dispute is that terms used by contemporaries tend to be misleading. Thus, the two parties which are said to have dominated the Long Parliament during the 1640s are known by descriptive names (“the Presbyterians” and “the Independents”) that the bear little resemblance to their actual platforms.